The Health Benefits of Grapefruit Furanocoumarins - Yu Wang; Laura E. Reuss (EDIS, 2018)
Although contraindicated for certain medications, grapefruits are also known for their numerous health benefits. Both these effects come from, in part, natural chemicals called furanocoumarin.  Numerous studies have shown that furanocoumarins, reduce inflammation and stop cancer cells from multiplying. Furthermore, they may also help repair damaged DNA that would otherwise contribute to the development of tumors.